A Comparative Analysis of Patient Satisfaction following Total Knee Arthroplasty and Total Hip Arthroplasty Using the Forgotten Joint Score - Singh, Vivek; Zak, Stephen; Schwarzkopf, Ran; Davidovitch, Roy (The Journal of Hip Surgery, 2020)
Measuring patient satisfaction and surgical outcomes following total joint arthroplasty remains controversial with most tools failing to account for both surgeon and patient satisfaction in regard to outcomes. The purpose of this study was to use “The Forgotten Joint Score” questionnaire to assess clinical outcomes comparing patients who underwent a total hip arthroplasty (THA) with those who underwent a total knee arthroplasty (TKA). We conducted a retrospective review of patients who underwent primary THA or TKA between September 2016 and September 2019 and responded to the Forgotten Joint Score-12 (FJS-12) questionnaire at least at one of three time periods (3, 12, and 21 months), postoperatively. An electronic patient rehabilitation application was used to administer the questionnaire. Collected variables included demographic data (age, gender, race, body mass index [BMI], and smoking status), length of stay (LOS), and FJS-12 scores. t-test and chi-square were used to determine significance. Linear regression was used to account for demographic differences. A p-value of less than 0.05 was considered statistically significant. Of the 2,359 patients included in this study, 1,469 underwent a THA and 890 underwent a TKA. Demographic differences were observed between the two groups with the TKA group being older, with higher BMI, higher American Society of Anesthesiologists scores, and longer LOS. Accounting for the differences in demographic data, THA patients consistently had higher scores at 3 months (53.72 vs. 24.96; p < 0.001), 12 months (66.00 vs. 43.57; p < 0.001), and 21 months (73.45 vs. 47.22; p < 0.001). FJS-12 scores for patients that underwent THA were significantly higher in comparison to TKA patients at 3, 12, and 21 months postoperatively. Increasing patient age led to a marginal increase in FJS-12 score in both cohorts. With higher FJS-12 scores, patients who underwent THA may experience a more positive evolution with their surgery postoperatively than those who had TKA.
Keywords: patient-reported outcome; total hip arthroplasty; total knee arthroplasty; Forgotten Joint Score; FJS-12